2016
DOI: 10.1021/acs.analchem.6b03515
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Modified Gold Nanoparticles for Sensitive Colorimetric Detection of Pb2+ Ions in Rainwater Polluted by Leaking Perovskite Solar Cells

Abstract: In the past few years, the advent of lead halide perovskite solar cells (PSCs) has revolutionized the prospects of the third- generation photovoltaics and the reported power conversion efficiency (PCE) has been updated to 22%. Nevertheless, two main challenges, including the poisonous content of Pb and the vexing instability toward water, still lie between the lab-based PSCs technology and large scale commercialization. With this background, we first evaluated Pb concentration from the rainwater samples pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…However, we have bear in mind that Sn element is still harmful to the human body in their practical utilization,224, 225 while Bi, Sb, and Cu are more environmentally friendly. Finally, we should think about our initial question: can we get the clean power output from the new hybrid absorbers without the danger of environmental contamination?226 The answer may need to be found in the future development of new lead‐free hybrid light harvesting materials.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have bear in mind that Sn element is still harmful to the human body in their practical utilization,224, 225 while Bi, Sb, and Cu are more environmentally friendly. Finally, we should think about our initial question: can we get the clean power output from the new hybrid absorbers without the danger of environmental contamination?226 The answer may need to be found in the future development of new lead‐free hybrid light harvesting materials.…”
Section: Discussionmentioning
confidence: 99%
“…Most extrinsic factors can destroy the device in a relatively short timescale, while intrinsic factors usually are working during a longer timescale. Firstly, in a few seconds, the device can be failed upon exposure to bulk water 72 . Then under working conditions, the voltage bias can lead to macroscopic migration of a large amount of I − ion in minutes 73 .…”
Section: Stability Enhancement With Mdpmentioning
confidence: 99%
“…19 Afterward, the appearance of Au-S bond at ~ 296 cm -1 and disappearance of S-H bond at ~ 2524 cm -1 in the Ramon spectrum of GSH-AuNPs revealed that GSH was successfully modified to the surface of AuNPs (Figure 2d). 11 Transmission electron microscopic (TEM) image showed that the as-prepared GSH-AuNPs was spherical and monodisperse (Figure2b), which was displayed an average hydrodynamic size of 13.5 ± 0.8 nm in aqueous solution acquired by the dynamic light scattering analysis (DLS, Figure 2c). In view of these results, we then investigated the preparation process of SPG7/AuNPs probe by titration experiments.…”
Section: (Figure 1) 3 Results and Discussionmentioning
confidence: 99%
“…10 Beside, Nazeeruddin et al prepared GSH-AuNPs self-assembled sensors for the analysis of Pb 2+ which produced by halogenated lead-halide perovskite solar cells (PSCs) with a detection limit of 15 nM. 11 In particular, Tseng and co-workers developed a colorimetric detection of Pb 2+ by controlling the particle size, particle size distribution of gallic acid-capped gold nanoparticles (GA-AuNPs) and minimizing electrostatic repulsion between each GA-AuNP, the lowest detection limit is 10 nM. 12 Despite the great success and the ongoing increase of interest with AuNPs-based colorimetric assays, most of them were dependent on AuNPs as the starting color indicator, which may somehow lower signal-to-background ratios and hence weaken the detection sensitivities.…”
Section: Introductionmentioning
confidence: 99%